Citizen participation, information-technology communication and public opinion (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
Citizen participation today is also related to information technology and communication (ICT), allowing the citizen expresses opinions, attitudes , publicly as a member of a community in matters of common interest. This user participation covers an infinite set of realities that can have a strictly personal and / or social relationship, with the intent of sharing ideas and political views among all potential users of the Network this dissertation an epistemic approach was attempted opinatica this dynamic city . The method used is the literature review, with the theoretical postulates delimitation: Cunill (1991-1995-1997), Martinez (1996) and Hernandez (2007, 2010), among others. It is evident that there is intense use of process tools hypertext content that promotes citizen participation mainly in relation to public and political expressions.
Keywords: citizen participation; information technology; communication and public opinion